-6(3x+9)+7=

Simple and best practice solution for -6(3x+9)+7= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6(3x+9)+7= equation:


Simplifying
-6(3x + 9) + 7 = 0

Reorder the terms:
-6(9 + 3x) + 7 = 0
(9 * -6 + 3x * -6) + 7 = 0
(-54 + -18x) + 7 = 0

Reorder the terms:
-54 + 7 + -18x = 0

Combine like terms: -54 + 7 = -47
-47 + -18x = 0

Solving
-47 + -18x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '47' to each side of the equation.
-47 + 47 + -18x = 0 + 47

Combine like terms: -47 + 47 = 0
0 + -18x = 0 + 47
-18x = 0 + 47

Combine like terms: 0 + 47 = 47
-18x = 47

Divide each side by '-18'.
x = -2.611111111

Simplifying
x = -2.611111111

See similar equations:

| 25p+6p^2=-4 | | x^4+4x^3+(-8x^2)+2=0 | | x^2-4x+13=29 | | -3-5x=-18 | | x^4+4x^3(-8x^2)+2=0 | | .5(4x+13)+.5= | | Log(3)(x+1)-log(3)x=2 | | t+9=-5 | | 32r^2-50=0 | | 7/x+5-1/x-3=5/3 | | -2-a=-2 | | r+6=6 | | x^4+4x^3-8x^2+2=0 | | .5(2x+4)+9= | | 1/2t^2-16=0 | | -80=-8x | | j-92=-20 | | 6x+3+2x-9x+10x=6+7+4x-9 | | 64b^2=4 | | 4y^2+52y+169=0 | | -2-n=-5 | | 1.50/8 | | d-47=42 | | 132=-12r | | 132=12r | | x-33=-52 | | 2*+4=6 | | n-84=16 | | t-33=-51 | | 3x+88=7x+36 | | 7x+30=2x+130 | | x^2+0.75x+0.125=0 |

Equations solver categories